26S proteasome subunits are O-linked N-acetylglucosamine-modified in Drosophila melanogaster. - Sumegi, M.; Hunyadi-Gulyas, E.; Medzihradszky, K.F.; Udvardy, A. (Biochemical and Biophysical Research Communications, 2003)
The O-linked glycosylation of highly purified Drosophila 26S proteasome has been analyzed by immunological and lectin-binding methods. Five regulatory complex subunits and at least nine catalytic core subunits were recognized by two different monoclonal antibodies specific for O-linked N-acetylglucosamine-modified proteins, and by wheat germ agglutinin, which is specific for the N-acetylglucosamine sugar side-chain. The specificity of these reactions has been proved by competition studies with free N-acetylglucosamine. Three ATPase subunits of the regulatory complex, which are O-glycosylated, have previously been shown [FEBS Lett. 430 (1998) 269] to occur in phosphorylated form as well, indicating that several different post-translational modifications, with distinct regulatory potential, may be present on the same subunit.